ANALISIS KEPEMIMPINAN DALAM MENINGKATKAN KEDISIPLINAN KARYAWAN PADA PT. ITK - Muhammad Hengki Hermawan; Heru Baskoro (Universitas Sarjanawiyata Tamansiswa, 2023)
The purpose of this research is to find out and explain the leadership analysis whose job is to direct and improve employee discipline at PT. ITK which is located in Dradah Blumbang Village, Kedungpring District, Lamongan Regency, East Java. Leadership in the company is expected to be a driving force that has an important role in the continuity of organizational activities so that the level of employee discipline increases and avoids work accidents. This type of research is qualitative research with interviews, documentation and field observations. The results of the analysis show that the leadership style applied is a democratic leadership style where employees are involved in making decisions. The leadership strategy implemented by making written regulations, conducting K3 training and providing strict sanctions for violators of disciplinary rules.